2016
DOI: 10.5966/sctm.2015-0274
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretching Promotes Skin Tissue Regeneration via Enhancing Mesenchymal Stem Cell Homing and Transdifferentiation

Abstract: Skin tissue expansion is a clinical procedure for skin regeneration to reconstruct cutaneous defects that can be accompanied by severe complications. The transplantation of mesenchymal stem cells (MSCs) has been proven effective in promoting skin expansion and helping to ameliorate complications; however, systematic understanding of its mechanism remains unclear. MSCs from luciferase-Tg Lewis rats were intravenously transplanted into a rat tissue expansion model to identify homing and transdifferentiation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 38 publications
3
42
0
3
Order By: Relevance
“…By inhibiting each of these processes, this network subsequently could not be seen in vitro , proving that this signaling network is the key component to cell differentiation via environmental change [104]. Other studies suggest that mechanical stretching can even regenerate skin tissue [105]. Stretching could upregulate gene expression related to cell proliferation, vascularization, etc.…”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…By inhibiting each of these processes, this network subsequently could not be seen in vitro , proving that this signaling network is the key component to cell differentiation via environmental change [104]. Other studies suggest that mechanical stretching can even regenerate skin tissue [105]. Stretching could upregulate gene expression related to cell proliferation, vascularization, etc.…”
Section: Biophysical Regulation Of Cell Reprogrammingmentioning
confidence: 99%
“…The concentration of HIF-1α in the skin before the start of the dermotension was (Me [Q1; Q3]) 110 [98,1; 114,8] ng/ml. A statistically significant increase in the concentration of 2; 221,7] ng/ml (p=0.008) recorded in the group of animals who underwent tissue stretching within 30 minutes, research also showed that the concentration of 4; 463,3] ng/ml (p=0.007) after 24 hours from the start of the dosed strains. Conclusion.…”
mentioning
confidence: 73%
“…Концентрация HIF-1α в коже до начала дермотензии составляла (Ме [Q1; Q3]) 110 [98,1; 114,8] нг/мл. В группе животных, которым выполняли тканевое растяжение в течение 30 минут зафиксировано статистически значимое увеличение концентрации 2; 221,7] нг/мл (р=0,008), через 24 часа от начала дозированного растяжения, выявлено,4; 463,3] нг/мл (р=0,007). Вывод.…”
unclassified
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs) are widely distributed in the tissues of bone marrow, fat, periosteum, muscle, synovium, tendon, umbilical cord blood, pulp, peripheral blood vessels. The isolated mesenchymal stem cells can be separated from these tissues with multiple differentiation potential, with high self-renewal ability and proliferation ability [5]. It can differentiate into bone, cartilage, fat, muscle, tendon, vascular endothelial cells and nerve cells under different induction and differentiation conditions.…”
Section: Introductionmentioning
confidence: 99%